671 Fetus-In-Fetu Found at Excision of An Antenatally Diagnosed Abdominal Mass: Multi-Disciplinary Approach. (12th October 2021) - Smith, K; Moore, A; Popov, S; Adams, M; Folaranmi, E; Sekaran, P
Abstract: We present a case of antenatally detected abdominal mass and an alternative diagnostic course for suspected neonatal neuroblastoma as a result of investigative findings. A female infant presented antenatally with a left upper quadrant mass initially managed as a suspected neonatal neuroblastoma; further cross-sectional imaging suggested a wider differential including teratoma and aided surgical planning. The multi-disciplinary team (MDT) decision was for an early excision at 31 days and post-operative histology identified a diagnosis of fetus-in-fetu (FIF). We describe this case as a compliment to the current literature and an example of a necessary variation to recognised diagnostic and treatment pathways as a result of investigative findings.